Building a low cost advanced driver assistance system : human detection - Tan, Yan Ling (2016)
Driving safety has always been a top priority in the automotive industry. Advance Drive Assistance Systems (ADAS) are systems which helps driver in their driving process can enhance manufacturers’ competitiveness in the market. In the past decade, more emphasis has been placed on using such systems on driverless vehicles. As such, the development of ADAS is highly sought after in the industry. ADAS comprises of multiple sub-systems to operate and this project will aim to look into the human detection system for ADAS.